2015
DOI: 10.5815/ijitcs.2015.12.01
|View full text |Cite
|
Sign up to set email alerts
|

The Choice of the Best Proposal in Tendering with AHP Method: Case of Procurement of IT Master Plan’s Realization

Abstract: Abstract-The computer system has become one of the centerpieces in the functioning of organizations hence the importance of an IT (Information Technology) master plan to manage its development. To find a provider for the IT master plan's realization, organizations are increasingly using tendering as the mode of awarding contracts.This article focuses on the use of multi-criteria decision-making method AHP for analysis and evaluation of tenders during the awarding of contracts of IT master plan's realization. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Considering the recent years, on the use of multi-criteria decision-making and similar methods for subcontractor selection, Acar [37] have proposed a model for the selection of subcontractors with the analytic network process. Diabagate et al [21] presented a method of determining the best bid for a tender by analytic hierarchy method. Oladapo and Odeyinka [22] compared multi-criteria decision-making methods with multi-attribute analysis and analytic hierarchy process methods in subcontractor or contractor selection and found that these two methods show little difference.…”
Section: Subcontractor Selection Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the recent years, on the use of multi-criteria decision-making and similar methods for subcontractor selection, Acar [37] have proposed a model for the selection of subcontractors with the analytic network process. Diabagate et al [21] presented a method of determining the best bid for a tender by analytic hierarchy method. Oladapo and Odeyinka [22] compared multi-criteria decision-making methods with multi-attribute analysis and analytic hierarchy process methods in subcontractor or contractor selection and found that these two methods show little difference.…”
Section: Subcontractor Selection Criteriamentioning
confidence: 99%
“…It can be determined by a questionnaire prepared by the company managers, which demonstrates all of the technical personnel participants' views about the reputation of the subcontractor firm. Management = f (experience year of management team) (21) For the case study, this value is the average score of the questionnaire result which examined the reputation of the candidate firms by views of the technical stuff of the contractor company with scores ranked from 1 to 4 (1 indicates the lowest and 4 indicates the highest reputation).…”
Section: Reputationmentioning
confidence: 99%
“…Sciancalepore et al (2011) presented a classification of multicriteria methods showing their strengths and weaknesses. Some applications of multicriteria methods, in particular, the analytic hierarchy process (AHP), on public procurement have been proposed in the literature: Diabagaté et al (2015) applied the AHP to select the best tender during the awarding of contracts for an IT master plan's realisation; Puri and Tiwari (2015) for a contractor selection decision Wang et al (2013), to weight decision criteria.…”
Section: Introductionmentioning
confidence: 99%